A Comparative Study of Steroid Injection With or Without Lignocaine in Treating Frozen Shoulder - Pandey, Alok; Shrestha, B; Shrestha, K M (Journal of Universal College of Medical Sciences, 2018)
BACKGROUND: Treatment of Frozen shoulder (Adhesive Capsulitis) is mainly nonoperative. Intra-articular steroid injections and physiotherapy are one of the most effective and useful treatment. Even though intra-articular steroid injections are very effective in inflammatory phase of the disease; patients are reluctant to move their affected shoulder for fear of pain. Thus, they do not follow exercise program properly resulting in poor outcomes.OBJECTIVE: If pain could be reduced, outcome of treatment can improve. Lignocaine, when combined with steroid injection, plays an important role in immediate improvement of pain and active range of motion thereby increasing the overall result. MATERIALS & METHODS: 100 patients with frozen shoulder were selected according to predetermined inclusion and exclusion criteria. After randomization by sealed envelope technique, patients were divided into Group A and Group B. Group A patients were injected with 2 ml (80 mg) of methylprednisolone and 3 ml of 1% Lignocaine, and Group B patients were injected with 2 ml (80 mg) of methylprednisolone and 3 ml of Distilled water in the affected shoulder via standard posterior approach. Then half an hour of standard shoulder range of motion (ROM) exercise regimen was performed under supervision. Pre injection and post injection pain level was scored by Visual Analogue Score (VAS) and Subjective satisfaction score (SSS). Shoulder exercises were taught and home based physiotherapy was carried out by patients themselves. They were also prescribed oral analgesics for 5 days and were followed at 1, 3, and 6 weeks. At every follow up visit, they were assessed for improvement via Constant-Murley Score (CMS).RESULTS: The mean age of this study in group A and group B was 56.46 years (SD 10.05) and 57.18 years (SD 8.87) respectively (P0.70). There were 31 male and 19 female in group A as compared to group B where there was 26 males and 24 females (P0.41). In both the groups, maximum number of patients presented at around 10 weeks. In both the groups left side dominated right side with equal frequency (33 left sides and 17 right sides) (P 1.00) and non dominant side outnumbered dominant side with near equal frequency (P 1.00). After the intervention, excellent result in SSS was observed only in group A whereas maximum patients of Group B had only fair result (42 patients). There was statistically significant difference between two groups in terms of pain; Activity of daily living (ADL) and Range of motion (ROM). Patients in group A were able to carry more weight than group B.   In CMS 1 and 6 week total, there was statistically highly significant difference between two groups. CONCLUSION: Even though steroid and physical exercises play important role in managing frozen shoulder, addition of lignocaine to steroid injection seems to be helpful. It relieves immediate pain on movement and improves exercise compliance thereby improving early outcomes. Evaluation of long term benefits of lignocaine injection needs further studies. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, Page: 22-28